(untitled) (Archives of Mechanics - Test, 2004)
A finite-difference analysis of transient free convection flow of a dissipative fluid past an infinite vertical porous plate is presented here. Velocity, temperature, skin-friction and Nusselt number are shown graphically and the effects of different parameters on the flow field are discussed.